Auditor human capital and financial misstatement: Evidence from China - Xingqiang Du; Jingwei Yin; Fei Hou (China Journal of Accounting Research, 2018)
In this study, we examine whether education, as an important component of the human capital of auditors, is related to the occurrence of financial misstatement, and investigate the moderating effect of professional experience. Using a sample of 16,651 firm-year observations from the Chinese stock market from 2003 to 2014, we find that the education level of signing auditors is significantly negatively associated with the likelihood of financial misstatement, which suggests that higher education can enhance the ethics and independence of auditors and mitigate the risk of financial misstatement. In addition, professional experience attenuates the negative relation between the education level of signing auditors and financial misstatement. Our findings are also robust to a variety of sensitivity tests, and our conclusions still hold after using a two-stage OLS-logistic regression to address the endogeneity problem. Lastly, the negative effect of education level on financial misstatement holds only for 985 Project universities, low individual-level (audit-firm-level) client importance, and state-owned enterprises.
Keywords: M42; J41; P36; 650; Auditor human capital; Financial misstatement; Education level; Professional experience; Signing auditors